Legal Policy Dynamics of the Foreign Workers in Indonesia: Should it be justified? - Nyoman Mas Aryani; Ayu Putu Laksmi Danyathi; Bagus Hermanto (Kertha Patrika, 2022)
The enactment of Presidential Regulation Number 20 of 2018 concerning the Use of Foreign Workers and Job Creation Law has triggered pros and cons. On the one hand, these arrangements define as advanced approach to increase investment in Indonesia and assist transfer knowledge that can be obtained from equipped foreign workers with their skills and technologies. There are substantial arrangements to ease foreign workers access under growth investment idea, facilitating business licensing through deregulation, and scrutinize legal provisions for foreign workers to be able to work in Indonesia. This article was aimed to analyze, and finding analysis of policy dynamics regulating the use of Foreign Workers in Indonesia, as well as the gaps of the use of Foreign Workers arrangement in the Job Creation Law. This article was normative legal research using statutory approach, and conceptual approach. The study indicated that the dynamics of regulation in various legal policies on the use of Foreign Workers especially between Law on Employment and Law on Job Creation, even though there are fields and types of work that are also required to prioritize Indonesian Workers, along with the use of Foreign Workers to a certain time limit to adopt Foreign Workers skills. The prospective policy direction through this article is expected to be more selective policy in the context of utilization of foreign workers, state protection, and adequate improvement quality/standard of competence for Indonesian workers.